A Concise Dictionary of Paleontology - Carlton, Robert L. (Springer International Publishing, 2018)
This authored dictionary presents a unique glossary of paleontological terms, taxa, localities, and concepts, with focus on the most significant orders, genera, and species in terms of historical turning points such as mass extinctions. The book is an accurate and up-to-date collection of the most important paleontological terms and taxa, and may be used as a resource by students, researchers, libraries, and museums. Though useful to many in professional and academic settings, the book is also aimed at general readers of scientific literature who may enjoy the material without a background in paleontology. While there are many current resources on the subject, few fully encapsulate an accurate representation of the paleontological lexicon. This book attempts to compile such a representation in a moderately comprehensive manner, and includes a list of the most important monographs and articles that have been consulted to put together this essential work.